Necessary conditions for the generation of acoustic solitons in magnetospheric and space plasmas with hot ions - Verheest, F.; Hellberg, M.A.; Lakhina, G.S. (My University, 2007)
Necessary conditions are discussed for the possible generation of large solitary acoustic modes in plasmas with one or more ion species which are hotter than some or all of the electron species. The analysis is based on a fluid dynamic approach. It is found that in most of these configurations the existence ranges for the solitary wave velocities are very narrow and close to one of the thermal velocities. In the latter situation, linear Landau damping may prevent the generation of nonlinear structures. The analysis indicates that both inertial and thermal effects for the ions need to be kept in the description, thus rendering an analytical investigation much more intricate.
Keywords: Acoustic solitons; Magnetospheric; Space plasma; Solitary waves; Plasma; Hot ions